NURSING THE NURSED: ADDRESSING COVID-19 PANDEMIC CRISIS IN THE CUEN THEORY PERSPECTIVE - Joel Rey Ugsang Acob (Belitung Nursing Journal, 2020)
Caring as an unending expression of nursing holds true this very time of trials. Humanity is faced with a crisis in the COVID-19 however healthcare professionals are standing still to save the world. This document illustrates how CUEN theory is applied in the care of patients undergoing emerging infectious diseases and stipulates its contribution to the care of patients having infected with the disease.